Reframing type 1 diabetes through the endocannabinoidome-microbiota axis: a systems biology perspective - Łukowski, Wojciech (Frontiers in Endocrinology, 2025)
Type 1 diabetes (T1D) has long been recognized as a T-cell-driven autoimmune disease. However, growing evidence highlights the involvement of metabolic, inflammatory, and gut microbiota-related factors in its progression. The endocannabinoid system (ECS), a key regulator of immune and metabolic homeostasis, has been increasingly implicated in autoimmune pathophysiology, particularly through its interactions with gut-derived metabolites. This hypothesis article underscores the need to reframe T1D pathophysiology by integrating ECS dysfunction, gut dysbiosis, and metabolic imbalances into a systems biology framework. The proposed Endocannabinoidome-Microbiota (ECBoM) model highlights a shared hallmark of autoimmunity—SCFA depletion, increased intestinal permeability, and ECS dysregulation—as key drivers of chronic inflammation and immune dysfunction. These disturbances, observed in T1D as well as in celiac disease, Hashimoto’s thyroiditis, rheumatoid arthritis, and multiple sclerosis, suggest a common immune-metabolic axis across autoimmune disorders. Recognizing ECS dysregulation as a systemic feature of autoimmunity opens avenues for novel therapeutic interventions, including ECS-targeted treatments, microbiota modulation, and phytocannabinoid-based therapies. This article highlights the necessity of conducting large-scale, multi-omics studies to establish disease-specific ECS signatures, linking endocannabinoid profiling, microbiota composition, and metabolic biomarkers to disease progression. By advocating for a paradigm shift in T1D research, this article emphasizes the importance of exploring new mechanistic references to develop targeted, immune-metabolic interventions that could reshape treatment strategies and improve clinical outcomes in T1D and related autoimmune diseases.